Rapid fuel switching from coal to natural gas through effective carbon pricing - Staffell,IL; Wilson,IAG (Nature Energy, 2018)
Great Britain’s overall carbon emissions fell by 6% in 2016, due to cleaner electricity production. This was not due to a surge in low-carbon nuclear or renewable sources; instead it was the much-overlooked impact of fuel switching from coal to natural gas generation. This Perspective considers the enabling conditions in Great Britain and the potential for rapid fuel switching in other coal-reliant countries. We find that spare generation and fuel supply-chain capacity must already exist for fuel switching to deliver rapid carbon savings, and to avoid further high-carbon infrastructure lock-in. More important is the political will to alter the marketplace and incentivize this switch, for example, through a stable and strong carbon price. With the right incentives, fuel switching in the power sector could rapidly achieve on the order of 1 GtCO2 saving per year worldwide (3% of global emissions), buying precious time to slow the growth in cumulative carbon emissions.